På fast grund: Om det äldsta stenkyrkobyggandet i Sigtuna - Tesch, Sten (Hikuin, 2006)
On solid foundation About the building of stone churches in the 12th century Sigtuna By Sten Tesch This study deals with the least known and discussed part of the church – the foundation wall. The discussion is about how to use the construction of the foundation wall as a means to separate the absolutely oldest romanesque churches from the others. In Sigtuna at least six stone churches were built in a very short period beginning around AD 1100. These are some of the oldest stone churches in Sweden. Small research excavations in connection with two of the churches have revealed that the upper parts of the foundation walls were partly walled with mortar. The evidence from the ruin church of S. Olof has been especially rewarding. Walls from a possible church or a part of a church older than the visible ruin was found inside. Both buildings had partly solid foundation walls. This method is in Scandinavia supposed to have been used only when the earliest stone churches were built. The use of solid foundation walls was soon abandoned in favour of foundations built up without mortar. This study also describes the development from Christian graveyards (sv. gravgårdar) to Romanesque churches in a sacred townscape. Almost from the beginning Sigtuna stands out as an out-and-out Christian place, where the elite could demonstrate a Christian identity. An almost continuous chain of graveyards, where people are buried according to Christian ritual, surrounds the settlement area. So far there are no traces of wooden churches, only secondary indications. A diocese, the first in the region, was established in Sigtuna c.1060 by the archbishop of Hamburg- Bremen. A cathedral was built in the middle of the town. All other churches were built along a new street, parallell and North to the main street Stora Gatan, and in the same area as the graveyards. The church topography reflects an intention to create a sacred townscape for ecclesiastical processions. It also reflects the idea of the holy and heavenly city. The last time a Sigtuna bishop is mentioned is in 1134. The Sigtuna bishopric must have ceased before 1164, when the bishopric in Old Uppsala became the archbishopric of Sweden. But Sigtuna remained an important ecclesiastical centre. In c.1215 the Pope gave the Church permission to move the archbishopric from Old Uppsala to Sigtuna, but the transfer was for unknown reasons never made. Two or three of the romanesque churches were demolished already in the the late 13th century due to the organisation of parishes in the Lake Mälaren region. The others were abandoned after the Reformation in the first half of the 16th century. Three of the churches now stand as ruins, the other three are only preserved as foundation walls below ground.